Menyikapi Keontentikan Hadis Dalam Perspektif Harald Motzki (Studi Isnad Cum Matan Harald Motzki): Id - Siddik Firmansyah (Program Studi Ilmu Hadis STAIN Mandailing Natal, 2022)
Currently, it is still being debated by orientalists about the truth of hadith as a source of Islamic history that is no longer authentically derived from the prophet, as well as the views and thoughts of orientalists in studying hadith such as Ignaz Goldziher and Joseph Schacht which had a great influence on western scientists. The purpose of this study is to repeat the hadith criticism that has been tested by classical hadith scholars that most of the hadiths are not fake as some orientalists understand, the method used is the descriptive analysis of isnad cum matn, in this study the author conducted research by contemporary orientalist Harald Motdzi who broke the previous orientalist hadith critique by proving that from the historical sanad and matn hadith in the book of Musannaf Abd Razaq as-San'ani, this study proves that most of the traditions that are sources of law and history are authentic from the Prophet.